Editorial - María Claudia Nieto Cruz; Melba Libia Cárdenas (Profile: Issues in Teachers' Professional Development)
In this edition we have gathered ten articles whose authors are spread over seven countries, namely: Argentina, Chile, Colombia, Mexico, New Zealand, Spain, and the United States. This diversity evidences not only the coverage of our readership, but the increasing interest of academic communities in the kinds of works we promote in PROFILE.